Labour's utopias revisited - Beilharz, Peter (2012)
This paper revisits a book I published 20 years ago. Labour's Utopias-Bolshevism, Fabianism, Social Democracy (Routledge, 1992) began from the proposition that utopia was a ubiquitous figure in Western political and social thinking. On the Left the common sense has often been that reform and revolution are but different proposed roads to the same utopian end. Labour's Utopias shows that this is not the case: Bolshevism, Fabianism and social democracy actually embody different ends. Revisiting the text 20 years later, my sense is that its most interesting and significant weakness lies not in its diagnosis of utopia, but in its failure to differentiate significantly between labour and its intellectual representatives. I hint at the issue of 'social' or 'socialist ventriloquism', but fail to follow it through. The issue of representation, or claims to representation, remains under-illuminated, as does the possibility that there are significant differences between working-class and middle-class utopias. © 2012 The Author(s).